Media literacy capabilities of broadcast monitoring in Regional Indonesian Broadcasting Commission (KPID) of West Java - Dedeh Fardiah,; Darmawan, Ferry; Rini Rinawati, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The role of media literacy is significantly needed to ward off the harmful effects of the media, especially television. Ideally, media literacy skills should be possessed by all people to avoid numerous harmful effects of television. The Indonesian broadcasting commission (KPI) as the broadcast regulator in Indonesia has the task of monitoring broadcast content and also educating the public to be media literate. In conducting its duties, it involves the community to monitor broadcasts by forming volunteers, known as broadcast monitors. This study uses a quantitative approach to examine accessibility, analysis, evaluation, and broadcast monitoring communication in supporting broadcast regulator performance. The research object is broadcast monitors supervised by the Regional Indonesian Broadcasting Commission (KPID) of West Java Province in 2018. The monitors consist of five batches from five regions in West Java, namely Sumedang, Subang, Karawang, Bogor, and Bandung. Based on the research results, it shows that the media literacy capability of broadcast monitors is high, both in terms of the ability to access the media, analyze television programs and evaluate them, and even communicate the results of their monitoring to KPID West Java. The high level of media literacy has decent implications for the high participation of broadcast monitors to make complaints and the frequent findings of violations related to broadcast contents.